Potentially inappropriate medications among older adults in Pelotas, Southern Brazil - Bárbara Heather Lutz; Vanessa Irribarem Avena Miranda; Andréa Dâmaso Bertoldi
ABSTRACT OBJECTIVE To assess the use of potentially inappropriate medications among older adults. METHODS This is a population-based cross-sectional study with 1,451 older individuals aged 60 years or more in the city of Pelotas, State of Rio Grande do Sul, Brazil, in 2014. We have investigated the use of medications in the last 15 days. Using the Beers criteria (2012), we have verified the use of potentially inappropriate medications and their relationship with socioeconomic and demographic variables, polypharmacy, self-medication, and burden of disease. RESULTS Among the 5,700 medications used, 5,651 could be assessed as to being inappropriate. Of these, 937 were potentially inappropriate for the older adults according to the 2012 Beers criteria (16.6%). Approximately 42.4% of the older adults studied used at least one medication considered as potentially inappropriate. The group of medications for the nervous system accounted for 48.9% of the total of the potentially inappropriate medications. In the adjusted analysis, the variables female, advanced age, white race, low educational level, polypharmacy, self-medication, and burden of disease were associated with the use of potentially inappropriate medications. CONCLUSIONS It is important to known the possible consequences of the use of medication among older adults. Special attention should be given to the older adults who use polypharmacy. Specific lists should be created with more appropriate medications for the older population in the National Essential Medicine List.